STEPHEN JOHNSON, ed., A Tyranny of Documents: The Performing Arts Historian as Film Noir Detective - Marini, Francesca (Archivaria, 2013)
A Tyranny of Documents: The Performing Arts Historian as Film Noir Detective. Performing Arts Resources, vol. 28. STEPHEN JOHNSON, ed. New York: Theatre Library Association, 2011. xiii, 353 p. ISBN 978-0-932610-24-9.